A combined catchment‐reservoir water quality model to guide catchment management for reservoir water quality control. (2nd March 2021) - Chen, Chi‐Feng; Chong, Kean‐Yip; Lin, Jen‐Yang
Abstract: In this study, the Hydrological Simulation Programme‐FORTRAN (HSPF) and the Water Quality Analysis Simulation Programme (WASP), were adopted as a combined tool. The long Feitsui impounding reservoir located in Taiwan was used as a case study. The combined model helped illustrate the total phosphorus (TP) mass balance. Approximately 51.4% of the TP flowed out from the reservoir, while 16.2% of the TP remained in the waterbody and 32.2% of the TP was deposited. The reservoir was divided into five sections along its length for a quality analysis. The exceedance probability (the probability of exceeding the eutrophic level, i.e., TP = 24 μg/L) was 9.7% in the upstream section. If the TP load increased by 20%, the eutrophication exceedance probability could increase to 25.5%. This study demonstrated the usage of the combined model tool and the exceedance probability method in the data analysis, which could guide effective catchment management and eutrophication risk prevention.